The neural correlates of memory encoding and recognition for own-race and other-race faces - Herzmann, Grit; Willenbockel, Verena; Tanaka, James W.; Curran, Tim (Neuropsychologia, 2011)
► Other-race effect is a memory encoding- and recognition-based phenomenon. ► Neural correlates of encoding are more efficient and elaborate for own-race faces. ► Neural correlates of recollection are more detailed for own-race faces. ► Neural correlates of recollection are more effortful for other-race faces. ► Retrieval of other-race faces requires active monitoring. People are generally better at recognizing faces from their own race than from a different race, as has been shown in numerous behavioral studies. Here we use event-related potentials (ERPs) to investigate how differences between own-race and other-race faces influence the neural correlates of memory encoding and recognition. ERPs of Asian and Caucasian participants were recorded during the study and test phases of a Remember–Know paradigm with Chinese and Caucasian faces. A behavioral other-race effect was apparent in both groups, neither of which recognized other-race faces as well as own-race faces; however, Caucasian subjects showed stronger behavioral other-race effects. In the study phase, memory encoding was assessed with the ERP difference due to memory (Dm). Other-race effects in memory encoding were only found for Caucasian subjects. For subsequently “recollected” items, Caucasian subjects showed less positive mean amplitudes for own-race than other-race faces indicating that less neural activation was required for successful memory encoding of own-race faces. For the comparison of subsequently “recollected” and “familiar” items, Caucasian subjects showed similar brain activation only for own-race faces suggesting that subsequent familiarity and recollection of own-race faces arose from similar memory encoding processes. Experience with a race also influenced old/new effects, which are ERP correlates of recollection measured during recognition testing. Own-race faces elicited a typical parietal old/new effect, whereas old/new effects for other-race faces were prolonged and dominated by activity in frontal brain regions, suggesting a stronger involvement of post-retrieval monitoring processes. These results indicate that the other-race effect is a memory encoding- and recognition-based phenomenon.